Wild is the witch - Griffin, Rachel, 1985- (Sourcebooks Fire, 2022)
When eighteen-year-old witch Iris Gray accidentally enacts a curse that could have dire consequences, she must team up with witch-hating Pike Alder to make sure her magic is not unleashed on the world.